1994
DOI: 10.1007/bf00293314
|View full text |Cite
|
Sign up to set email alerts
|

Corticobasal degeneration: etiopathological significance of the cytoskeletal alterations

Abstract: We have studied brain tissues from three patients with corticobasal degeneration (CBD) histologically, ultrastructurally and immunohistochemically. Ballooned neurons in the cerebral cortex and severe degeneration of the substantia nigra were observed in them all and weakly basophilic neurofibrillary tangles (NFTs) were distributed widely in the basal ganglia and brain stem. Ultrastructural examination demonstrated that the NFTs comprised characteristic 15-nm-wide straight tubules, which showed positive immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(64 citation statements)
references
References 32 publications
2
61
1
Order By: Relevance
“…b Those in the pyramidal neurons in the motor cortex were composed of STs, measuring 13-20 nm in diameter, and c those in the neurons of the nucleus centralis superior were composed of STs, 13-16 nm in diameter (STs straight tubules). Uranyl-lead, × 47,000 observed in CBD [11,26,37,43], were not seen in the present patient. From the view point of complications of PDC, granular hazy astrocytic inclusions, which have been observed in every patient with PDC [35], were not evident in the present patient.…”
Section: Discussioncontrasting
confidence: 41%
“…b Those in the pyramidal neurons in the motor cortex were composed of STs, measuring 13-20 nm in diameter, and c those in the neurons of the nucleus centralis superior were composed of STs, 13-16 nm in diameter (STs straight tubules). Uranyl-lead, × 47,000 observed in CBD [11,26,37,43], were not seen in the present patient. From the view point of complications of PDC, granular hazy astrocytic inclusions, which have been observed in every patient with PDC [35], were not evident in the present patient.…”
Section: Discussioncontrasting
confidence: 41%
“…Recently, it was reported that complicated cases have exhibited overlapping findings clinically and pathologically [3,12,18,19]. Furthermore, clinical diagnosis and pathological diagnosis are inconsistent with each other in some cases [6,10,11,24,25,27].A case whose clinical diagnosis does not correspond with pathological diagnosis is referred to as atypical CBD or PSP in this report. Pathological diagnosis of CBD and PSP is based on microscopic findings, but not gross findings according to the neuropathologic criteria [4,7,17].…”
Section: Introductionmentioning
confidence: 58%
“…Several atypical cases showed that microscopic findings of CBD or PSP extended beyond the specific areas for these diseases [3,6,10,18,19,24,25,27]. Degeneration with tau positive intranuclear inclusion in the nucleus of the aqua duct, locus ceruleus, pontine nucleus and dentate nucleus as well as the cerebrum were reported in the atypical CBD cases [18,19,25,27]. In contrast, the precentral cortical degeneration was reported in PSP cases [8,9,23].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations